2014
DOI: 10.1163/15685373-12342107
|View full text |Cite
|
Sign up to set email alerts
|

Corpses, Maggots, Poodles and Rats: Emotional Selection Operating in Three Phases of Cultural Transmission of Urban Legends

Abstract: PostprintThis is the accepted version of a paper published in Journal of Cognition and Culture. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination. Citation for the original published paper (version of record):Eriksson, K., Coultas, J. (2014) Corpses, maggots, poodles and rats: Emotional selection operating in three phases of cultural transmission of urban legends. Journal of Cognition and Corpses, maggots, poodles and rats: Emotional selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(132 citation statements)
references
References 48 publications
4
126
1
1
Order By: Relevance
“…Previous studies have shown that people are likely to remember and share emotionally salient information [31,32,57]. Individuals who report voting based on their emotional reaction to content give Empathy / Humour especially high importance.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that people are likely to remember and share emotionally salient information [31,32,57]. Individuals who report voting based on their emotional reaction to content give Empathy / Humour especially high importance.…”
Section: Resultsmentioning
confidence: 99%
“…A result replicated by several independent labs is that information about social relationships is transmitted with higher fidelity than equivalent non-social information (McGuigan and Cubillo 2013; Mesoudi et al 2006;Reysen et al 2011;Stubbersfield et al 2014), as predicted by social brain theories of the biological evolution of primate cognition (Dunbar 2003). There is also experimental support for a bias for emotionally salient disgust-inducing information (Eriksson and Coultas 2014;Heath et al 2001). Xu et al (2013), meanwhile, found that initially random colour terms transmitted along chains of people gradually converged on those colour terms commonly seen across actual societies, arguing that the innate features of our perceptual system makes certain colours more salient and thus more likely to emerge through repeated transmission.…”
Section: Cognitive Biases Can Drive Cultural Evolution Towards Culturmentioning
confidence: 91%
“…There is merit in this argument: after all, the capacity for culture evolved genetically because it increased inclusive fitness, as explored by numerous gene-culture coevolution analyses Richerson 1985, 1995). Moreover, many of the cognitive biases discussed above have putative inclusive fitness benefits, such as keeping track of social relationships (Mesoudi et al 2006) and learning about disease-carrying substances (Eriksson and Coultas 2014). Others (myself included) have argued that non-genetic forms of inheritance such as cultural evolution can additionally constitute ultimate causes of behaviour and thus require a rethinking of the original proximate-ultimate scheme (Danchin et al 2011;Laland et al 2011;Mesoudi et al 2013).…”
Section: Is Culture Proximate or Ultimate?mentioning
confidence: 99%
See 1 more Smart Citation
“…Having passed through long transmission chains from one individual to another, they should bear the mark of all these minds' proclivities and biases. Researchers in the field of cultural evolution posit that cultural transmission is more likely to maintain stories with emotional content, a prediction largely confirmed both by experimental and by observational data (Eriksson & Coultas, 2014;Eriksson, Coultas, & de Barra, 2016;Heath, Bell, & Sternberg, 2001;Stubbersfield, Tehrani, & Flynn, in press). Emotional words are thought to enhance memorability (Doerksen & Shimamura, 2001;Kensinger & Corkin, 2003;Levine & Pizarro, 2004;Talmi & Moscovitch, 2004).…”
mentioning
confidence: 89%